The influence of carrot juice on the quality indicators of wheat bread from the first grade flour - S. N. Edygova; Z. N. Khatko; A. A. Teknedzhan (Новые технологии)
The article presents the results of research on the effect of carrot juice on the quality of wheat bread made from first-grade flour. Possibilities of using the potential of vegetables of the Republic of Adygea, in particular carrots, to obtain carrot juice and use it in the technology of wheat bread from 1st grade flour. The positive effect of carrots on the human body has been studied. Compared to the main raw material, carrot juice does not lose its properties, it has an equally rich chemical composition that can effectively influence the properties of yeast dough and improve wheat bread quality, as well as increase its nutritional value. Physical and chemical indicators of carrot juice have been defined. In the course of the study the positive effect of carrot processing products, namely carrot juice, on technological properties of wheat flour has been proved. Organoleptic characteristics of baked wheat bread samples have been studied: control, samples enriched with 50% and 100% carrot juice. The use of juice during kneading has showed acceleration of the lifting force of yeast, improving its technological properties and imparting a functional orientation. The diagrams of the effect of carrot juice on the lifting power of dry yeast have been built. Physicochemical parameters of the samples of 1st grade wheat bread enriched with carrot juice have been studied. On the basis of the data obtained, a draft technical documentation has been developed for «Bread from 1 grade wheat flour, enriched with carrot juice».